Time reproduction deficits in essential tremor patients. Issue 8 (19th April 2016) - Pedrosa, David J.; Nelles, Christian; Maier, Franziska; Eggers, Carsten; Burghaus, Lothar; Fink, Gereon R.; Wittmann, Marc; Timmermann, Lars
ABSTRACT: Background: Although motor symptoms predominate in essential tremor, increasing evidence indicates additional cognitive deficits. According to the pivotal role of cognitive functioning for temporal information processing and acknowledging the relevance of temporal information processing for movement coordination, we investigated whether essential tremor patients exhibit time reproduction deficits. Methods: A total of 24 essential tremor patients and 24 healthy controls performed sub‐ and suprasecond visual duration reproduction tasks of 500 to 900 milliseconds and 1.6 to 2.4 seconds, respectively. To differentiate deficient time processing from motor or other cognitive dysfunctions, the average temporal reproduction errors were correlated with tremor severity, immediate and delayed word‐list recall performance, and verbal fluency. Results: Essential tremor patients significantly underreproduced sub‐ and suprasecond time intervals longer than 800 milliseconds. Moreover, time compression correlated significantly with semantic verbal fluency and word‐list retrieval performance, but not with tremor severity. Conclusion: Data suggest impaired temporal processing in essential tremor, corroborating evidence for specific cognitive deficits. © 2016 International Parkinson and Movement Disorder Society